Dependent person in self‐care: analysis of care needs. Issue 3 (21st October 2019) - Dixe, Maria dos Anjos Coelho Rodrigues; Frontini, Roberta; Sousa, Pedro Miguel Lopes; Peralta, Teresa de Jesus de Almeida; Teixeira, Liliana Fernanda da Conceição; Querido, Ana Isabel Fernandes
Abstract : Background: The aim of this study was to assess the self‐care dependency levels of the dependent person at the time of home discharge and its relationship between (1) the degree of dependency of each self‐care domain; (2) the previous dependency levels; and (3) the gender of the dependent person. It also aims to assess the relationship between the degree of dependency of each self‐care domain, the length of admission, the length of dependency and the age of the dependent person at the time of discharge. Methods: A cross‐sectional study was conducted. The sample comprised hospitalised adults and elderly in the medical services of a Portuguese hospital during the months of March, April and May of 2018. The data were collected by an interview conducted at the time of home discharge from the hospital medical ward. Results: The average age of dependent people of the sample is 80.7 years (±10.1) with the majority being women (51.7%), with no statistical difference in the mean age according to gender (U = 2205.500; p > 0.05). They were hospitalised on average 11.4 days (±33.2), most of them (44.0%) due to respiratory problems (85% of which were due to pneumonia). There were no statistically significant differences between the length of the hospital stay, the length of dependency and the participants' gender (U = 2200.500, p > 0.05; U = 1688.000, p > 0.05). Medication intake was the highest dependency domain amongst participants (41.3%), followed by instrumental activities of daily living (40.6%) and bathing (39.9%). Conclusion: The amount of support required may vary according to the domain that the person is dependent. Thus, it is important to use a robust and reliable assessment tool that will be able to assess the degree of dependency on the various domains of self‐ care.